PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MELALUI MEDIA WORDWALL PADA MURID KELAS III SEKOLAH DASAR - Hamdani; Hastya Rantna Ningayu; Tria Ambarwati; Ruri Novia Setiani; Nurul Hidayatul Jannah; Eka Sariana; Ricka Tesi Muskania (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low academic achievement of students in the Pancasila Education subject in Class IIIB at SD Negeri 34 in Pontianak City District. This low achievement is attributed to instruction that remains dominated by lecture-based methods and the limited variety of instructional media used, resulting in suboptimal student engagement in the learning process. This study aims to improve learning outcomes in Pancasila Education through the use of Wordwall media for third-grade students in Class IIIB at SD Negeri 34 in Pontianak City District. The method used is Classroom Action Research (CAR) based on Kurt Lewin’s model, which consists of four stages: planning, action, observation, and reflection. The study was conducted in two cycles with 31 students as research subjects. Data collection techniques included observation and achievement tests. Data were analyzed using quantitative and qualitative descriptive methods. The results indicate that the use of the Wordwall medium was effective in improving learning outcomes in Pancasila Education. The percentage of students achieving mastery increased from 45.36% in the pre-cycle to 58.06% in Cycle I and further increased to 80.64% in Cycle II. Additionally, the use of Wordwall also improved student motivation, participation, and active engagement during the learning process. Thus, the Wordwall platform can serve as an effective alternative learning tool to enhance learning outcomes in Pancasila Education at the school.